KINERJA IMPLEMENTASI LOAD BALANCING DENGAN METODE PCC PADA PENGGUNAAN WIRELESS NETWORK - Adji Surya Dinata; Eka Purwa Laksana (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
Load balancing is one of the routing techniques by utilizing several Internet Service Providers (ISP) to be used simultaneously or back up each other if other ISPs are down or in trouble. There are various methods that can be used, one of which is the PCC method on wireless networks. Peer Connection Classifier (PCC) is one method that can be used in load balancing. PCC can be used to group connection traffic through a proxy router into several groups. So the router will remember the path that was passed at the beginning of the connection traffic and in subsequent packets that are still related to the connection initially will be passed on the same path as well. In this implementation, the test uses the Winbox application to analyze and monitor network traffic. Then speedtest.net is used to measure the performance of Wireless Network Quality Of Service (QOS) both by testing bandwidth, jitter, delay and using the wireshark application as monitoring throughput at each ISP. This load balancing testing scenario is done by downloading data of 94.13 MB, 133.68MB and 302.26 MB. For testing carried out three times in the morning with a time interval of 07:00 to 08:00, during the day with a time interval of 13:00 to 14:00 and the night with a time interval of 24:00 to 01:00. The implementation of the load balancing system aims to make the link more stable by distributing traffic loads on two or more connection lines in a balanced way, maximizing throughput, minimizing delays and avoiding overload. The highest increase in average throughput occurred at night conditions by downloading 302.26 MB of large capacity data which was 7.7 Mbps.